Resolving Seasonal Ice Velocity of 45 Greenlandic Glaciers With Very High Temporal Details. Issue 3 (9th February 2019) - Vijay, Saurabh; Khan, Shfaqat Abbas; Kusk, Anders; Solgaard, Anne M.; Moon, Twila; Bjørk, Anders Anker
Abstract: Seasonal glacier ice velocities are important for understanding controlling mechanisms of ice flow. For many Greenlandic glaciers, however, these measurements are limited by low temporal resolution. We present seasonal ice velocity changes, melt season onset and extent, and ice front positions for 45 Greenlandic glaciers using 2015–2017 Sentinel‐1 synthetic aperture radar data. Seasonal velocity fluctuations of roughly half of the glaciers appear to be primarily controlled by surface melt‐induced changes in the subglacial hydrology. This includes (1) glaciers that speed up with the onset of surface melt and (2) glaciers with comparable late winter and early melt season velocities that show significant slowdown during most of the melt season and speedup during winter. In contrast, less than a quarter of the study glaciers show strong correspondence between seasonal ice speed and terminus changes. Our results pinpoint seasonal variations across Greenland, highlighting the variable influence of meltwater on year‐round ice velocities. Plain Language Summary: Many Greenlandic glaciers are marine‐terminating and seasonal fluctuations in the ice velocity influence ice discharge timing and magnitude. We used Sentinel‐1 satellite data to observe seasonal changes in ice velocities, ice front positions, and surface melt conditions for 45 Greenlandic glaciers during 2015–2017, capturing substantial temporal detail. Seasonal velocity variations of nearly half of the glaciers show the strongest correlation with surface melt changes, which seasonally alter the subglacial hydrology. In contrast, less than a quarter of the study glaciers show strong correspondence between seasonal ice velocities and seasonal advance and retreat of the glacier ice front. This study highlights the strong potential influence of surface meltwater on the ice velocities of many Greenlandic glaciers. Key Points: Sentinel‐1 radar data pinpoint seasonal ice velocity variations with high temporal details Surface melt‐induced changes in subglacial hydrology control seasonal ice flow of many glaciers Seasonal ice flow of ten of the sampled glaciers respond primarily to seasonal terminus changes